Threats and regulatory protection of Asian elephants in Peninsular Malaysia - Lee, Ee Ling (2016)
Asian elephants have been categorised as “endangered” in the International Union for Conservation of Nature (IUCN) Red List of Threatened Species 2015 and Appendix I of Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). As Malaysia is one of the Asian elephant range states, it is imperative to investigate the main threats to Asian elephants. Furthermore, the ratification of CITES and Convention on Biological Diversity (CBD) in 1975 and 1992 respectively targets conservation of biodiversity with more than 100 signatories, including Malaysia. Yet, few studies related are known. Hence, this study uses data to analyse the main threats, as well as the extent of legislation addressing them. The study also identifies CBD and CITES obligations related to Asian elephant conservation; Wildlife Conservation Act 2010 (WCA) was analysed against the CBD obligations and International Trade in Endangered Species Act 2008 (INTESA) was examined against CITES obligations. Primary data from interviews and secondary data were gathered and analysed with inductive and deductive thematic content analysis. The results reveal that human elephant conflict (HEC), land use change and poaching are three main threats to Asian elephants. The conversion of forests into plantations and human-dominated areas are the causes of HEC and land use change. Given that land use change has reduced elephant habitats, farmers suffer in HEC (eg. crop loss, property damages, human injuries and deaths). HEC also leads to retaliatory killing and intolerable coexistence between elephant and human. Meanwhile, the high demand and monetary return from ivory trade, including poverty and corruption, are the causes of poaching, which ultimately skew the sex ratio between male and female elephants. WCA regulates elephants’ trade, poaching, possession and breeding through license, permit and special permit while INTESA monitors elephants’ trade, captive breeding and transit, with permit, certificate and registration. WCA also monitors elephant habitats and HEC by gazetting protected areas (PAs) and HEC mitigation measures respectively. Nevertheless, the amount of fine and period of imprisonment imposed to offences involving elephants bred in captivity are less compared to similar offences involving wild elephants. Hence, INTESA imposes higher fine and period of imprisonment to such offences. In addition, the CBD obligations related to Asian elephant conservation covers protection and conservation of elephant habitats and its genetic resources; sustainable use of biodiversity; the access to and benefits sharing from utilisation of elephant’s genetic resources; and the access to and transfer of technology. Generally, WCA addresses the CBD obligations through similar regulations addressing habitat loss and HEC. However, WCA does not regulate the access to and transfer of technology. Besides that, CITES obligates trade regulation of species in Appendix I; form of permit and certificate; and measures to be taken by parties. Permit to elephant trade and captive breeding for commercial purposes will only be approved if trade is not detrimental and for non-commercial purposes. However, INTESA permits captive breeding for commercial purposes and import permit is not compulsory for export and re-export. Appropriate treatment should be given to living elephants in trade, but INTESA only obligates adequate care of imported and captivated elephants in Malaysia. To this end, the main threats to Asian elephants and the compliance of Malaysian legislation to international environmental conventions are addressed. However, legislation revisions and amendments are needed.